Find the minimum value m and the maximum value M of f ( x , y , z ) = x 3 + 4 y 3 + 9 z 3 when x + y + z = 1 2 , where x , y and z are non-negative real numbers. Enter m + M .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Oh, yes, that's one of the quick ways to do it (+1)
how did u prove the second part of the question that deals with maximum
Since the function is convex, we can use Jensen's inequality:
f ( x , y , z ) = x 3 + 2 ( 2 y ) 3 + 3 ( 3 z ) 3 ≥ 6 ( 6 x + y + z ) 3 = 6 ∗ 2 3 = 4 8 = f ( 2 , 4 , 6 ) = m
Again, since the function is convex, the maximum M must be attained at one of the vertices; checking the three cases we see that M = f ( 1 2 , 0 , 0 ) = 1 7 2 8 .
Thus the required sum is M + m = 1 7 7 6
I'm going to find the minimum value via Applying the Arithmetic Mean Geometric Mean Inequality and the maximum value via differentiation followed by Second derivative test.
We are given that x + y + z = 1 2 . Apply AM-GM on the numbers { x 3 , x 3 , x 3 , 8 , 8 , 8 , 8 , 8 , 8 } , we get 9 3 x 3 + 6 ⋅ 2 3 ≥ 9 x 9 ⋅ 2 1 8 ⇒ x 3 + 1 6 ≥ 1 2 x ( 1 ) .
Similiarly, apply AM-GM on the numbers { y 3 , y 3 , y 3 , 6 4 , 6 4 , 6 4 , 6 4 , 6 4 , 6 4 } , we get 4 y 3 + 1 2 8 ≥ 1 2 y ( 2 ) .
And again, for the numbers { z 3 , 2 1 6 , 2 1 6 } , we get 9 z 3 + 4 3 2 ≥ 1 2 z ( 3 ) .
Adding these 3 inequalities and apply the fact that x + y + z = 1 2 , we get x 3 + 4 y 3 + 9 z 3 ≥ 4 8 .
Equality holds when x = 2 , y = 4 , z = 6 . Thus the minimum value is 48.
Now for the maximum value, we must check on the boundary values:
Case 1
:
x
=
0
only.
Case 2
:
y
=
0
only.
Case 3
:
z
=
0
only.
Case 4
:
x
=
y
=
0
only.
Case 5
:
x
=
z
=
0
only.
Case 6
:
y
=
z
=
0
only.
It's easy to check that for Case 4, 5, 6, the value of the expression is question are 192, 432, 1728 respectively.
For Case 1 , the constraint simplifies to y + z = 1 2 , and we want to maximize 4 y 3 + 9 z 3 . Apply the substitution of z = 1 2 − y onto the expression 4 y 3 + 9 z 3 and differentiate it shows that its maximum value is 2 5 1 7 2 8 . And we can prove that it's a maximum value via Second Derivative Test.
Analogously, we can solve for Case 2 and 3, which yield the maximum value of 108 and 192 respectively.
Hence from all these 6 cases, the maximum value of the expression in question is 1728 at y = z = 0 , x = 1 2 .
Minimum: When the terms are similar, you should check if you could have a similar approach. For example, why did you use { x 3 , x 3 , x 3 , 8 , 8 , 8 , 8 , 8 , 8 } but { z 3 , 2 1 6 , 2 1 6 } ? You could have just used { x 3 , 8 , 8 } and { z 3 , 2 1 6 , 2 1 6 } , which makes the approach less mysterious.
Maximum: I don't see any stated application of differentiation followed by second derivative test. It is not immediately apparent why the max must occur on the boundary.
Clear systematic solution (+1).
The extrema you find in Cases 1 through 3 are minima, not maxima, I believe... they have to be, since the function is convex.
Problem Loading...
Note Loading...
Set Loading...
By Holder's Inequality, ( x 3 + 4 y 3 + 9 z 3 ) ( 1 + 2 + 3 ) ( 1 + 2 + 3 ) ≥ ( x + y + z ) 3 = 1 2 3 , so x 3 + 4 y 3 + 9 z 3 ≥ 6 2 1 2 3 = 4 8 . Equality occurs when ( x , y , z ) = ( 2 , 4 , 6 ) .
Also, x 3 + 4 y 3 + 9 z 3 ≤ ( x + y + z ) 3 = 1 7 2 8 . Equality occurs when ( x , y , z ) = ( 1 2 , 0 , 0 ) . Thus, the minimum is 48 and the maximum is 1728.